Issues in Scientific Terminology in African / Bantu Languages - (:unkn) unknown (My University, 2007)
In 2006, the South African Department of Education initiated a pilot project in which the Matric or Senior Certificate papers for Science, Maths, Biology and History were translated into the nine official African/Bantu languages of the country. Grade 12 learners who use these languages as home languages therefore received a question paper containing questions in English, where every question was followed by its translation into the relevant language. Taking into consideration that these learners received their tuition in these subjects through the medium of English, the rationale behind this project was to assist learners in the decoding of the English questions by providing them with a translated version in their respective home languages. Our discussion focuses specifically on the issue of the translation of technical terminology in the Sepedi papers1, and is based on data collected for a research project aimed at evaluating the impact of this project on learners' performance, done under the auspices of CentRePoL.
Keywords: African Research